PENDIDIKAN SAINS: IBADAH UNTUK MELESTARIKAN KEMAMPUAN LINGKUNGAN YANG MENDUKUNG PEMBANGUNAN - Supardi, Kasmadi Imam (Badan Pengembang Konservasi UNNES, 2012)
Human beings are special and chosen creatures. Special from their body composition, and chosen because thei are given the duty as leaders to prosper the Earth. As a leader, human beings are given the intelligence and by using their intelligence they are able to master science. The application of science is technology. Technology can be used to preserve their environmental ability, which means with science and technology human beings can prosper the Earth, but vice versa there are science and technology applications which bring harm to the environment, if it is not build based on religious values. In developing the nature, human beings cannot preserve the environment or preserving the environmental balance, because ecologically the use of natural resources for the development is a disturbance itself towards the environmental balance. Therefore, the one thing that human beings can preserve is the environmental ability to support the development as well as a better living. In order to do so, it is substantially important to have human beings who are capable of managing the environment, those who posses a loving character as well as scientific knowledge about nature.Manusia adalah makhluk istimewa dan makhluk pilihan.Ã‚Â Istimewa dalam susunan tubuhnya, dan makhluk pilihan karena diberi tugas sebagai khalifah untuk memakmurkan bumi. Sebagai khalifah, manusia diberi akal dan dengan akalnya manusia bisa menguasai sains. Aplikasi sains adalah teknologi. Teknologi bisa dimanfaatkan untuk melestarikan kemampuan lingkungan, artinya dengan sains dan teknologi, manusia bisa memakmurkan bumi, namun bisa sebaliknya, ada aplikasi sains dalam teknologi yang bisa merusak kemampuan lingkungan, jika tidak didasari oleh nilai-nilai agama. Dalam pembangunan di alam, manusia tidak bisa melestarikan lingkungan atau melestarikan keseimbangan linkungan, karena secara ekologi penggunaan sumber daya alam untuk pembangunan adalah gangguan terhadap kesetimbangan lingkungan. Jadi, yang bisa dilestarikan oleh manusia ialah kemampuan lingkungan untuk mendukung pembangunan dan tingkat hidup yang lebih baik. Untuk itu diperlukan manusia pengelola lingkungan yang baik, yakni mereka yang memiliki akhlak yang baik dan memiliki pengetahuan tentang sumberdaya alam yang memadai.